Official netscape navigator 4 book :The definitive guide to the world's most popular internet browser windows - James, Phil.; Wyke, R. Allen ([S.l.] : Ventana Pr, 1997)
Readers will learn Intranet, extranet, and Internet technologies. Includes sections on Navigator 4 installation, interface, customization, and basic browsing. Shows how to view graphics, sound, and video.